Transcutaneous bilirubin measurement in healthy Saudi term newborns - Alsaedi, Saad A. (Saudi Med J, 2016)
OBJECTIVES: To evaluate the accuracy of transcutaneous bilirubin (TcB) measurement in healthy, jaundiced Saudi term newborns. METHODS: This prospective, cohort study was carried out from January 2009 to December 2012 on jaundiced, term infants admitted at the King Abdulaziz University Hospital, Jeddah, Kingdom of Saudi Arabia. Paired TcB and total serum bilirubin (TSB) from healthy jaundiced term newborns were obtained. The correlation and the mean difference between the 2 methods were calculated, and Bhutani nomogram for prediction of TSB by TcB was used. Any bilirubin level at low and above the intermediate risk zone was considered significant. RESULTS: We obtained 665 paired TcB and TSB measurements from 665 newborns. The mean age at bilirubin measurement was 44.2 ± 21 hour. Mean TSB was 147 ± 45 µmol/L, and TcB was 156 ± 50 µmol/L. Linear regression analysis showed a significant correlation between TcB and TSB (r: 0.84; 95% confidence interval [CI] = 0.82-0.86; p<0.001). The TcB tends to overestimate TSB. The mean difference between paired TcB and TSB was 17 µmol /L with a 95% CI of 40 ± 77 µmol/L. The TcB was sensitive, but less specific. The TcB sensitivity was 83% and specificity was 71% to predict TSB during the first 72 hours of life for the whole study group. The positive predictive value was 63%, and negative predictive value was 87%. CONCLUSION: As found in this study, among the jaundiced healthy term Saudi newborns, TcB measurement provided accurate estimates of TSB values. The TcB measurements can be used effectively to screen newborns for significant jaundice.